P257Relationship between 24h urinary sodium with blood pressure, arterial elasticity and urine protein in hypertensive patients. (15th July 2014) - Sun, N; Han, W; Zhao, L; Liu, X; Chen, Y; Wang, H
Abstract: Objective: To investigate the effects of hypertensive patients with high salt intake on blood pressure, arterial elasticity and microalbuminuria. Methods: 341 untreated patients with hypertension were collected. 24-hour urinary sodium (24HUNa) excretion, blood pressure, microalbuminuria and baPWV were observed in these patients. All of the patients were divided into three groups according to their 24h urinary sodium excretion (mmol/24h): A group (low urinary sodium, ≤100mmol/24h) of 93 cases, B group (medium urinary sodium, 100<24HUNa≤200mmol/24h) of 171 cases and C group (high urinary sodium, 200mmol/24h) of 77 cases. Results: The 24h urinary sodium excretion (mmol/L) in three groups were 78.6±17.9, 146.7±26.9 and 254.7±41.8, corresponding to daily salt intake (g/day) were 4.7, 8.8 and 15.2, respectively. The baPWV(cm/s) in high urinary sodium group was obviously higher than in low urinary sodium group (1753.5±303.8 vs 1604.9±339.9, P=0.028). Meanwhile, the increased level of blood pressure and microalbuminuria in high urinary sodium group were statistically higher than in the other two groups. In addition, multiple regression analysis showed that urinary sodium was an independent factor of baPWV(B=0.583 P=0.021). Urinary sodium had positive correlation with excretion of urinary protein (B=1.235 P=0.027). Conclusions: Our study demonstrated that high sodium intake was independently associated with target organ damage. High sodium in coordination with hypertension can aggravate target organ damage.